(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was designed to collect some information about the sorghum stemborer in the Nuba Mountains, South Kordofan State. It was carried out during 2005/06and 2006/07 season, to determine the population dynamics and the alternative host plantsof the stem borer. Light trap was used for adult trapping, and a survey was carried out forhost plants. The number of adults was low at the beginning of the season (June),gradually increased towards the end of the season (October) and the borer disappearedby the end of November. Night activity of the adults was low at 7:00 pm and increasedgradually towards 10:00 pm. The highest infestation by stem borer (76%) was recordedon sorghum (Sorghum bicolor L.) followed by Sorghum arundinceum (adar) (63%),maize, Zea mays (50%) and pearl millet (33%)